Challenges and opportunities for eliminating tuberculosis - leveraging political momentum of the UN high-level meeting on tuberculosis - Haruka Sakamoto; Sangnim Lee; Aya Ishizuka; Eiji Hinoshita; Hiroyuki Hori; Nanao Ishibashi; Kenichi Komada; Masataro Norizuki; Yasushi Katsuma; Hidechika Akashi; Kenji Shibuya (BMC, 2019)
Abstract Background As demonstrated by the United Nations High-Level Meeting on tuberculosis (TB) held in September 2018, the political momentum for TB has been increasing. The aim of this study was to analyze the current challenges and opportunities for global TB control and, with specific focus on policies surrounding TB control, to reveal what kinds of efforts are needed to accelerate global TB control. Methods We organized two expert meetings with the purposes of assessing the current situation and analyzing challenges regarding TB control. By applying Shiffman and Smith's framework which contains four categories; Actor, Ideas, Political context, and Issue characteristics, we analyzed the challenges and opportunities for global TB control based on the findings from the two expert meetings. Results In the Actor Category, we found that although there has already been active engagement by non-governmental organizations (NGOs), civil society organizations (CSOs) and private sectors, there still remained an area with room for improvement. In particular, the complexities behind varying drug regulatory and procurement systems per country hindered the active participation of the private sector in this area. As for the Ideas category, due to an increasing threat of antimicrobial resistance and growing number of global migrations, TB is now widely recognized as a health security issue rather than a purely health issue. This makes TB an easier target for political attention. As for the Political category, having the UN High-Level Meeting itself is not enough; such meetings must be followed up by actual commitments from heads of states. Lastly the issue characteristic indicates that the amount of funding for R&D for new drugs, vaccines and diagnostics for TB is not at an adequate level, and investment in childhood TB and missing cases are particularly in need. Conclusions This study provides important insight into the current status of global efforts toward end TB epidemic. The outcomes from the UN high-level meeting on TB need to be closely monitored will be crucial for the progress towards this goal.